2023
DOI: 10.3390/cancers15235527
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Joinpoint Analysis of Cancer Incidence and 1-Year Mortality in North-East Spain 2005–2020

Pere Roura,
Emma Puigoriol,
Jacint Altimiras
et al.

Abstract: Cancer is the second leading cause of death. It is thus essential to examine cancer trends in all regions. In addition, trend data after 2019 and on cancer 1-year mortality are scarce. Our aim was to analyze incidence and 1-year mortality cancer trends in northeastern Spain during 2005–2020. We used the Osona Tumor Registry, which registers cancer incidence and mortality in Osona. The mortality information came from the Spanish Death Index. We analyzed age-standardized incidence rates and 1-year mortality by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the statistical power of these studies was limited owing to small sample sizes. A study utilizing an extensive database from northeastern Spain revealed a decrease in the incidence of GC; however, the mortality remained unchanged from 2019 to 2020 [33]. Notably, in this previous study, patients who succumbed to the disease were not necessarily diagnosed during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 63%
“…However, the statistical power of these studies was limited owing to small sample sizes. A study utilizing an extensive database from northeastern Spain revealed a decrease in the incidence of GC; however, the mortality remained unchanged from 2019 to 2020 [33]. Notably, in this previous study, patients who succumbed to the disease were not necessarily diagnosed during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 63%